ETHOS JAKO FORMA PERSWAZJI RETORYCZNEJ W UJĘCIU ARYSTOTELESA - Gondek, Maria Joanna (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Мария Иоанна Гондек. Этос как форма риторического убеждения, согласно Аристотелю. Путь убеждения в риторической коммуникации характеризуется и определяется рациональными аргу- ментами, эмоциональными, и теми, которые ссылаются на моральный облик оратора. Согласно Ари- стотелю аргументация с помощью отношения к оратору делается из убедительных элементов, как на- пример: здравый смысл, добродетель, и доброжелательность. Реализация убеждения с помощью мо- рального отношения взаимосвязана с человеческой деятельностью, природа, которой, есть – согласно Аристотелю – подчинена результату, который является добром. Maria Joanna Gondek. Ethos as a form of the rhetoric persuasion, according to Aristotle. A way of persuasion in a rhetoric communication is being characterized and defined by the rational arguments (logos), the emotional ones (pathos), and by those that refer to the moral attitude of the orator. According to Aristotle the argumentation with a help of the attitude of the orator is being made of the persuasive elements such as: good sense (phrónesis), virtue (areté), and goodwill (eunoia). Thanks to them the orator finds the proper premises so he makes up the argumentation by stressing on the credibility of his own attitude or of the characters he is telling about. The basic difficulty that can show up as to the interpretation of the ethos by Aristotle is the overlapping of the potential aspect (ethos as a skill, i.e. dynamis) and the actual aspect (ethos as the actual and concrete persuasion with a help of the moral attitude of the orator). The realization of persuasion with a help of the moral attitude is being interrelated with a human activity the nature of which is — according to Aristotle — subordinated to the final, which is a good. Keywords: persuasion, ethos, good sense, virtue, goodwill.